Computational Thinking in Mathematics Education Across Five Nations - Suarsana, I Made; Herman, Tatang; Nurlaelah, Elah; Irianto; Pacis, Estrella R. (Universitas Pendidikan Ganesha, 2024)
Computational Thinking (CT) has been declared as the basic literacy of the 21st century, as well as reading literacy and numeracy literacy. Awareness about the importance of ICT has been responded very well by various countries by including CT in the school curriculum. This study aimed to analyze the comparison of the integration of CT in mathematics education in 5 countries, namely China, Singapore, United Kingdom (UK), Canada and the United States of America (USA). This study used a systematic literature review method that was carried out with the PRISMA protocol. This study started from identifying the process, assessing, and interpreting all available research evidence. The design used is to summarize, review, and analyse 43 articles in the Scopus database that are very relevant to the research object. The results of the study found that, most research on the integration of CT in mathematics education had been conducted in the USA. The type of research conducted in China was dominated by quantitative research while in Canada and it tended to be qualitative. In China, UK, Canada and USA, most of the research was carried out at the Elementary School level, while in Singapore was carried out at the Junior High School level. This result implies valuable insights for policymakers and educators regarding effective strategies for integrating CT in mathematics learning.